Optimization of NVH Performance of Electric Vehicle Reducers Based on Gear Transmission Error - Yu Ziqiang; Yu Hui; Yu Renping (Jixie chuandong)
Electric vehicle reducer gears have a wide range of torque speed when working, and transmission errors of gear pairs are different under different speed and torque conditions. In order to optimize the noise,vibration and harshness (NVH) performance of the reducer, the transfer error is optimized and improved for the common speed segment and common torque segment of electric vehicles. Firstly, Abaqus and Masta software are used to model and analyze the transmission error under different speed and torque conditions. Then, the gear is modified based on the data of common speed and torque conditions, and the transmission error after modification is analyzed. Finally, the modification effect is obtained by comparing the vibration and noise test of the reducer. The results show that the reducer runs at the usual speed and torque most of the time, the noise of the reducer is reduced by about 5 dB（A） and the NVH performance of the reducer is optimized by modification based on the transmission error data in this working condition.